2015
DOI: 10.1002/ece3.1511
|View full text |Cite
|
Sign up to set email alerts
|

Exploring seascape genetics and kinship in the reef sponge Stylissa carteri in the Red Sea

Abstract: A main goal of population geneticists is to study patterns of gene flow to gain a better understanding of the population structure in a given organism. To date most efforts have been focused on studying gene flow at either broad scales to identify barriers to gene flow and isolation by distance or at fine spatial scales in order to gain inferences regarding reproduction and local dispersal. Few studies have measured connectivity at multiple spatial scales and have utilized novel tools to test the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 68 publications
3
60
4
Order By: Relevance
“…Inbreeding analysis detected a significant heterozygosity deficit in most localities, indicating that they were not in HWE, a situation widespread among most studied sponges (Duran et al , 2004; Blanquer and Uriz, 2010; Dailianis et al , 2011; Pérez-Portela et al , 2015; Chaves-Fonnegra et al , 2015; Giles et al , 2015) and many other marine benthic invertebrates in the same geographical area (see, for example, Addison and Hart, 2005; Pérez-Portela and Turon, 2008; Mokhtar-Jamaï et al , 2013; Pérez-Portela et al , 2016). One of the reasons for deviations from HWE in marine invertebrates may be associated with the production of planktonic sperm for fertilization (Addison and Hart, 2005), the reproductive strategy of sponges (Maldonado and Riesgo, 2008).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Inbreeding analysis detected a significant heterozygosity deficit in most localities, indicating that they were not in HWE, a situation widespread among most studied sponges (Duran et al , 2004; Blanquer and Uriz, 2010; Dailianis et al , 2011; Pérez-Portela et al , 2015; Chaves-Fonnegra et al , 2015; Giles et al , 2015) and many other marine benthic invertebrates in the same geographical area (see, for example, Addison and Hart, 2005; Pérez-Portela and Turon, 2008; Mokhtar-Jamaï et al , 2013; Pérez-Portela et al , 2016). One of the reasons for deviations from HWE in marine invertebrates may be associated with the production of planktonic sperm for fertilization (Addison and Hart, 2005), the reproductive strategy of sponges (Maldonado and Riesgo, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, determining the genetic diversity and level of connectivity in sponge populations of this species is crucial when designing management strategies to prevent its extinction. Sponge populations are usually highly structured in ‘stable conditions' (that is, healthy populations), with relatively low gene flow and high levels of inbreeding (see, for example, Duran et al , 2004; Dailianis et al , 2011; Chaves-Fonnegra et al , 2015; Giles et al , 2015; Pérez-Portela et al , 2015). Therefore, even in ‘stable conditions' the recovery of sponge populations after massive reduction of the effective population size can be limited by their own biology, dispersal potential and oceanographic currents, and one could even predict lower recovery rates in stressed populations.…”
Section: Introductionmentioning
confidence: 99%
“…Over 20 years ago, Roberts et al (1992) found differences in the assemblage structure of coral reef fishes along the SA Red Sea coastline, which they ascribed to the marked increase in turbidity and changes in coral community structure south of~20°N. More recently, two independent studies identified patterns of genetic isolation in the southern Red Sea in both a coral reef fish and a reef sponge (Nanninga et al, 2014;Giles et al, 2015). Both studies demonstrated a strong correlation of biophysical gradients with genetic structure along the SA Red Sea coastline.…”
Section: Elasmobranch Diversitymentioning
confidence: 93%
“…Microsatellite data indicated a barrier for gene flow around the Farasan Islands separating the southern from the central and northern Red Sea S. carteri populations. Such a barrier could not be explained with the regional currents alone and provided the first evidence for a latitudinal environmental gradient influencing sponge population genetic structure (Giles et al, 2015). The more conservative 28S and CO1 data from S.…”
Section: Implications For Distribution Of Red Sea Sponge Taxamentioning
confidence: 96%
“…We obtained sequences from 34 samples making it the most frequently collected and amplified species in this study. Stylissa carteri was originally described from the Gulf of Manaar (Dendy, 1889) and recently was the subject of a comprehensive study of population genetic structure in the Red Sea (Giles et al, 2015). Microsatellite data indicated a barrier for gene flow around the Farasan Islands separating the southern from the central and northern Red Sea S. carteri populations.…”
Section: Implications For Distribution Of Red Sea Sponge Taxamentioning
confidence: 99%